Time frequency analysis of ultrasound doppler signal by s-transform and wigner-ville distribution - Mahieddine Latfaoui; Fethi Bereksi Reguig (Institute of Advanced Engineering and Science, 2019)
Ultrasound Doppler signal processing is a necessity in several disciplines of medicine. The interpretation of these signals allows a good diagnosis of patients in order to detect certain diseases. In this work, we will use different non-parametric time-frequency techniques such as the Wigner-Ville distribution (WVD), the Pseudo-Wigner-Ville distribution (PWVD), the smoothed pseudo Wigner-Ville distribution (SPWVD), and the S-transform in order to analyze the Ultrasonic Doppler signal of the femoral arteries.